Assessing agro-hydrological models to schedule irrigation for crops of Mediterranean environment - Blanda F.; Provenzano G.; Rallo G.; Minacapilli M.; Agnese C. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
The objective of the paper is to assess the possibility of using agro-hydrological models for irrigation scheduling, in order to optimize the water use efficiency. The results of a comparison between the numerical SWAP model and the functional model proposed by FAO to estimate water requirements in two typical arboreal Mediterranean Crops (grapevine and olive) are showed. In the initial phase of the research, involving both irrigation seasons 2005 and 2006, after a preliminary analysis of soil hydraulic and biophysical plant parameters, two intensive field measurements campaigns were carried out to measure the soil water content at different depths, to proceed to the validation of both models by means of the comparison between measured and predicted soil water content. Finally different irrigation scheduling options were examined, in order to compare the scheduled irrigation times with those planned by the farmers. The results of investigations put in evidence that FAO model simulates reliably the values of average water content of the soil profile, even if a certain overestimation of evapotranspiration fluxes can be observed with the FAO 56 model compared with SWAP. Consequently, the FAO model anticipates the starting date for irrigation obtained with SWAP, but, in terms of seasonal water requirements, the estimates determined by the two models did not result significantly different.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)